STRUCTURAL MODEL OF A QUASI-DIFFERENTIAL CALORIMETER - Воробйов, Леонід; Декуша, Леонід; Скляренко, Евгений; Іванов, Сергій (SWorldJournal, 2024)
The structure and transmission block diagram of a quasi-differential calorimeter, which allows simulation of processes in such a device, is proposed. The method of setting up a multi-reference quasi-differential calorimetric tool is considered. As an exa